Urban Dynamics and Insecurity in The Age of Digital Technology In Nigeria - Ahmed , Ibrahim (Corpus Intellectual, 2025)
The opening years of the twenty-first century were characterized by various form of security challenges in Nigeria which ranges from ethnic violence, religious crises, violent extremism, banditry, and kidnappings to mention but a few. All these aforementioned constitute or comprise the nature and trends of urban violence especially in Nigeria. However, in recent times, digital technology has been used or is been used by different agents of the underworld as well as other social movements to communicate violence, and transmit uncensored videos and audio either for genuine grievances against the state or existing social structure or for propaganda and to further create fear and insecurity in the minds of their targeted audience and those of the general public. This paper seeks to explore the conveniences or otherwise of the use of digital technology and also unearth some of the urban dynamics and drivers of insecurity in the age of digital technology. The capacity of digital technologies to spread incitement to ethnic hatred or public order offense, to promote religious and ethnic-based intolerance, and to consolidate identity-based schisms that are capable of stirring up conflicts offline, is unsurpassable. The complex and compelling interconnection of the heterogeneous set-up that is Nigeria’s social fabric, can promptly trigger conflicts. When driven by digital technologies, these happen at much faster rates. This is quite obvious from the #Endsars protest, the campaigns against the Fulani herdsmen, as well as Boko Haram insurgency and Banditry. For this paper, the terms ICT and digital technology will be used interchangeably.